Pre-clinical efficacy of a C4BP hexameric IgG Fc fusion protein against Neisseria gonorrhoeae - Jutamas Shaughnessy; Jintang Du; Mary Wakim Broden; Sunita Gulati; Bo Zheng; Nancy Nowak; Gretchen Telford; Sandy P. Fontes; Y. Tran; Keith L. Wycoff; Kevin J. Whaley; Alison K. Criss; et al. (PLOS One, 2026)
Gonorrhea is the second most common bacterial sexually transmitted infection and affects about 80 million people worldwide annually. The causative agent, Neisseria gonorrhoeae , has become resistant to almost every antibiotic used for its treatment. There is no licensed vaccine against gonorrhea. Therefore, there is an urgent need to develop novel prevention and treatment strategies to curb the spread of gonorrhea. The gonococcus has evolved several mechanisms to evade complement, a key arm of immune defenses against this pathogen, including binding of the human complement inhibitors Factor H (FH) and C4b-binding protein (C4BP). We previously showed that chimeric molecules fusing the gonococcal binding domains of FH and C4BP to IgG Fc and IgM Fc, respectively, mediate complement-dependent killing of gonococci in vitro and attenuate gonococcal colonization of mouse vaginas when administered topically. Here, we fused C4BP domains 1 and 2, which contain the gonococcal binding region, to IgG Fc bearing the IgM tail-piece to facilitate Fc hexamerization. This molecule, called C4BP-Hexa IgG Fc, showed ~650-fold greater complement-dependent bactericidal activity on a molar basis than monomeric C4BP-IgG1 Fc. C4BP-Hexa IgG Fc enhanced association with and uptake by human neutrophils in a complement-independent manner. Despite ‘off-target’ complement activation in solution, C4BP-Hexa IgG Fc reduced both the duration and the bacterial burden of gonococcal vaginal colonization in human FH and C4BP transgenic mice when administered intravaginally daily. In conclusion, we show proof-of-concept of the efficacy of a hexameric C4BP IgG Fc fusion molecule against N. gonorrhoeae , which could aid in the fight against this multidrug-resistant pathogen.